PENYULUHAN TERKAIT STRES DAN MEKANISME COPING SKILL - Bheby Jebriela; Cynthia Halim; Hartanti Hartanti (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Adolescence stage is known as ‘strom and stress’ phase. Changes in biological, cognitive, affective, and social functions can also be a problem and cause stress for teenagers. Even with high levels of stress experienced by teenagers, they often do not know what they have and how to manage their stress. The lack of coping skills in teenagers makes the way the cope less effective. This research provides counseling related to stress and how coping can be done effectively for teenagers. The subjects in this research were 20 teenagers who were members of the ROCKET community. The result is it is succeeded in increasing participants’ knowledge related to stress and effective coping methods. The particiants succeeded in reducing their stress level and half of the participants were encouraged to do more effective coping skills.